\[\boxed{\mathbf{859\ (859).\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[b_{n}^{2} = b_{n - 1} \cdot b_{n + 1};\ \ \ \ \ \ \ n > 1\]
\[\frac{b_{n}}{b_{n - 1}} = \frac{b_{n + 1}}{b_{n}}\text{\ \ }\]
\[то\ есть:\ \]
\[\text{\ \ }\frac{b_{2}}{b_{1}} = \frac{b_{3}}{b_{2}} = \frac{b_{4}}{b_{3}} = \ldots = \frac{b_{n}}{b_{n - 1}} =\]
\[= \frac{b_{n + 1}}{b_{n}} = q - это\]
\[\ геометрическая\]
\[\mathbf{последовательность.\ Начиная\ }\]
\[\mathbf{со\ второго\ члена,\ член\ равен}\]
\[\mathbf{\ предыдущему,}\]
\[\mathbf{умноженному\ на\ одно\ и\ то\ }\]
\[\mathbf{же\ число.}\]
\[\boxed{\mathbf{859.\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[1)\ b_{5} = - \frac{16}{27},\ \ q = - \frac{2}{3},\]
\[\text{\ \ }b_{1} - ?\]
\[b_{5} = b_{1}q^{4}\text{\ \ }\]
\[b_{1} = \frac{b_{5}}{q^{4}} = \frac{- 16 \cdot 3^{4}}{27 \cdot 2^{4}} =\]
\[= \frac{- 16 \cdot 81}{27 \cdot 16} = - 3\]
\[Ответ:\ b_{1} = - 3.\]
\[2)\ b_{1} = \frac{2}{3},\ \ b_{4} = \frac{9}{32},\ \ q - ?\]
\[b_{4} = b_{1}q^{3},\ \ q^{3} = \frac{b_{4}}{b_{1}},\]
\[\text{\ \ }q^{3} = \frac{9 \cdot 3}{32 \cdot 2},\ \ q^{3} = \frac{27}{64},\]
\[\ \ q = \frac{3}{4}\]
\[\mathbf{Ответ}:q = \frac{3}{4}\mathbf{.}\]
\[3)\ b_{7} = 192,\ \ q = 2,\ \ S_{7} - ?\]
\[b_{7} = b_{1}q^{6},\ \ \]
\[b_{1} = \frac{b_{7}}{q^{6}} = \frac{192}{64} = 3\]
\[S_{7} = \frac{b_{1}\left( q^{7} - 1 \right)}{q - 1} = \frac{3 \cdot \left( 2^{7} - 1 \right)}{2 - 1} =\]
\[= 3 \cdot (128 - 1) = 3 \cdot 127 = 381\]
\[Ответ:381.\]
\[4)\ b_{5} = 9\sqrt{6},\ \ q = \sqrt{3},\ \ \]
\[S_{5} - ?\]
\[b_{5} = b_{1}q^{4},\ \ \]
\[b_{1} = \frac{b_{5}}{q^{4}} = \frac{9\sqrt{6}}{9} = \sqrt{6}\]
\[S_{5} = \frac{b_{1}\left( q^{5} - 1 \right)}{q - 1} =\]
\[= \frac{\sqrt{6} \cdot \left( 9\sqrt{3} - 1 \right)}{\sqrt{3} - 1} =\]
\[= \frac{\sqrt{6} \cdot \left( 9\sqrt{3} - 1 \right)\left( \sqrt{3} + 1 \right)}{\left( \sqrt{3} - 1 \right)\left( \sqrt{3} + 1 \right)} =\]
\[= \frac{\sqrt{6} \cdot \left( 27 + 9\sqrt{3} - \sqrt{3} - 1 \right)}{3 - 1} =\]
\[= \frac{\sqrt{6} \cdot \left( 26 + 8\sqrt{3} \right)}{2} =\]
\[= \sqrt{6} \cdot \left( 13 + 4\sqrt{3} \right) =\]
\[= 13\sqrt{6} + 4\sqrt{18} = 13\sqrt{6} + 12\sqrt{2}\]
\[Ответ:13\sqrt{6} + 12\sqrt{2}.\]